Study on the adsorption mechanism and properties of silver-loaded zeolite for radioactive iodine - Shunlong Xu; Junjun Wang; Yaxin Feng; Yi Liu; Junteng Liu (Nuclear Materials and Energy, 2023)
Due to the continuous development of nuclear energy, a large number of radioactive elements will be produced during the treatment of nuclear waste and spent fuel, and the typical representative is radioactive iodine. Adopt to adsorb the radioactive iodine in the waste gas, the self-made silver-loaded zeolite was used to dynamically adsorb the radioactive iodine containing waste gas in this study. The adsorption effect of silver-loaded zeolite under different adsorption conditions, such as different linear velocity, different adsorption temperature, different pressure drops, different filler layer depth and other factors were studied. By exploring the experimental results, it can be seen that changing the different linear velocity in the adsorption column has little effect on the saturated adsorption competence of zeolite, and will affect the saturated adsorption time; Changing the filling depth of zeolite in the adsorption column will change the resistance in the adsorption process, affect the length of saturated adsorption time, and lead to the increase of its adsorption competence with the increase of the depth; The adsorption temperature of zeolite was controlled by controlling the ambient temperature of the adsorption column. It can be seen that the optimal adsorption temperature of zeolite is 150 ℃; Change the intake air flow to control its pressure drop, it can be seen that the pressure drops increases, the adsorption effect increases, and the adsorption time is shortened. The results of zeolite adsorption show that its adsorption competence is 52.05 ∼ 220.71 mg/g. Compared with other adsorption materials, zeolite has stable adsorption effect and low cost. It is a promising adsorbent with good industrial application prospects.